Insurance Coverage, and Having a Regular Provider, and Utilization of Cancer Follow-up and Noncancer Health Care Among Childhood Cancer Survivors - Michael R. Cousineau; Sue E. Kim PhD; Ann S. Hamilton PhD; Kimberly A. Miller PhD; Joel Milam PhD (SAGE Publishing, 2019)
The objective of this study was to assess the role of health insurance coverage on patterns of health care utilization and access to cancer-related follow-up and non-cancer care among childhood cancer survivors (CCS). Cross-sectional survey design was used. Childhood cancer survivors were from 2 large hospitals in Los Angeles County. In all, 235 were identified through the Los Angeles Cancer Surveillance Program, diagnosed between the ages of 5 and 18 in 2000-2007 with any cancer type except Hodgkin lymphoma. At data collection in 2009-2010, participants were between 15 and 25 years old. Study exposure was health insurance coverage (private, public, and uninsured). Main outcomes and measures were respondents' regular source of care for cancer follow-up, noncancer care, and both; and having a cancer follow-up visit, primary care visit, and hospital emergency department visit in the past 2 years. Compared with those with private insurance, the uninsured were less likely to have a regular source for cancer follow-up (odds ratio [OR] = 4.3, 95% confidence interval [CI] = 1.9-9.4), less likely to have a source for noncancer care (OR = 3.3, 95% CI 1.6-6.9), and less likely to have a source of care for both (OR = 5.3, 95% CI = 2.1-13.5). Furthermore, uninsured CCS were less likely to have made visits to cancer specialists (OR = 4.5, 95% CI = 2.1-9.50) and were less likely to have seen a primary care physician in the past 2 years (OR = 3.9, 95% CI = 1.8-8.2). In addition, those with public (vs private) insurance were less likely to have a regular provider for primary care (OR = 2.5, 95% CI = 1.1-5.4) and less likely to have made a primary care visit in the past year (OR = 2.8, 95% CI = 2.1-13.5). Uninsured CCS are at risk of not obtaining cancer follow-up care, and those with public (vs. private) insurance have less access to primary care. Policies that ensure continuity of coverage for survivors as they age into adulthood may result in fewer barriers to needed care, which may lead to fewer health problems for CCS in the future.